Gambaran Faktor Risiko Periprocedural Myocardial Injury pada Pasien Yang Menjalani IKP Elektif Di RSUD AWS Samarinda Periode Mei-Oktober 2019 - Khairun Nisa; Muhammad Furqon; Hary Nugroho (Jurnal Sains dan Kesehatan, 2020)
Periprocedural myocardial injury is one of complications after percutaneus coronary intervention that often occurs, and has a relationship with increased mortality. Several risk factors have been associated with the incidence of periprocedural myocardial injury. The purpose of this study was to determine the description of periprocedural myocardial injury risk factors which were divided into risk factors related to patients, lesions and procedures. The study was conducted with a prospective cohort research design and sampling by purposive sampling in March-October 2019. The number of samples was 38 people. The results showed that 31.6% sample experienced periprocedural myocardial injury. The description of risk factors in this study shows that patients with type-2 diabetes melitus more often experience periprocedural myocardial injury. As for other risk factors, the proportion of periprocedural myocardial injury is not greater than the proportion of non-periprocedural myocardial injury in patients with these risk factors. However, an increase in the proportion of periprocedural myocardial injury events occurs along with the increasing number of coronary arteries that have atherosclerotic lesions.